Knowledge, Attitude & Practices Related to Biomedical Waste Management Among the Nursing Staff of a Tertiary Care Rural Hospital of Gujarat, India - Kumar, Dinesh; Jayswal, Dipkala; Singh, Suman (National Journal of Community Medicine, 2016)
Background: Nurses constitute one of the largest and most important healthcare personnel category for biomedical waste generation (BMW) and handling. Methods: Cross-section study using an anonymous, semi-structured, self-administered, pre-tested questionnaire on BMW knowledge, attitude and practices. Results: Of the 300 respondents 262 (87.3%) were female, 247 (82.3%) had General Nursing and Midwifery qualification, 131 (43.6 %) worked in critical areas. The mean age was 29.8 (SD = 8.37) years, mean work experience was 7.38 (SD = 7.63) years. The scores in domain of policy knowledge was highest and institute specific knowledge was least. Overall knowledge about BMW was found to be better among female nurses (p=0.044). Positive attitude towards BMW management was significantly better among nurses working in critical care areas (p <0.001). Majority i.e. 288 (96.0%) nurses used personal protection equipment. The needle stick injury rate and needle recapping practices were 5% each. Needle stick injuries were more common among those working in critical area. 96% of the nurses had attended sessions on BMW management. Conclusions: BMW knowledge, attitude and practices among nurses were better than those reported in literature. However scope for further improvement in attitude and good practices does exist.